Coronavirus Disease 2019 Vaccine Booster Effects Are Seen in Human Milk Antibody Response - Bender, Jeffrey M.; Lee, Yesun; Cheng, Wesley A.; Marentes Ruiz, Carolyn J.; Pannaraj, Pia S. (Frontiers in Nutrition, 2022)
Infants remain at high risk for severe coronavirus disease 2019 (CoVID-19). Human milk contains high levels of protective SARS CoV-2 specific antibodies post-infection and primary vaccine series, but levels decline over time. We hypothesized that the CoVID-19 booster vaccine augment antibody production and the protection afforded to human milk-fed infants. We prospectively enrolled pregnant or lactating mothers planning to receive CoVID-19 vaccination. We measured human milk IgG, IgA, and IgM antibodies targeting the SARS CoV-2 receptor binding domain within the spike protein and human milk neutralization activity against SARS CoV-2 in 10 lactating mothers from pre-CoVID-19 primary series vaccine to post-booster dose. Human milk SARS CoV-2 specific IgG increased significantly from pre- to post-booster levels (median OD 0.33 vs. 2.02, P=0.002). The IgG levels post-booster were even higher than the peak level after the primary series (2.02 vs 0.95, P=0.03). The increase in SARS CoV-2 specific IgA levels was not significant (0.10 vs. 0.33, P=0.23). There was a strong correlation between paired maternal blood and milk IgG and IgA levels (IgG rho 0.52, P<0.001; IgA rho 0.31, P=0.05). Post-booster neutralizing activity was elevated compared to pre-booster levels (66% vs. 12% inhibition, P=0.002). CoVID-19 vaccine booster elicits SARS CoV-2 specific antibodies in human milk at higher levels compared to the initial primary series. This finding suggests that three doses of CoVID-19 mRNA vaccination leads to improved mucosal response in human milk and reinforces current guidance recommending all pregnant or lactating mothers receive full CoVID-19 vaccine courses with a booster dose.